Effects of altitude training on repeat sprint and graded exercise test performance in female road cyclists - Fornasiero, D.; Martin, D. T.; Brosnan, M. J.; Arkinstall, M. J.; Lee, H.; Trewin, C.; Moquin, A.; Stephens, S.; Gore, C. J.; Hanh, A. G. (1999)
The purpose of this study was to monitor the effects of an altitude training camp on cycling specific fitness using a graded exercise test (GXT) and a high-intensity repeat sprint test (RST). Ten members of the Australian Women`s National Road Cycling Squad (Mean± SD; 22.7± 4.3 yrs, 59.9± 3.8 kg 3.67± 0.28 L.min-1 VO2peak) completed an altitude training camp which involved living and training at 1600m for 7 d followed by a period of sleeping high (2700m) and training low (600m) for 10 days. Before and after the altitude training camp each cyclist performed a GXT, and a day later, a maximal 3x6 RST (3.5% TEM). The GXT began at 125 W and increased 25 W every 3-min until exhaustion. The RST involved 3 sets of 6 maximal, 15-sec sprints performed on a 1:3, 1:2 and 1:1 work:relief ratio (3 min recovery between sets). Power output (PO), oxygen consumption (VO2), and heart rate (HR) were monitored throughout each test. Blood lactate (HLA) and pH were measured from capillary blood samples. Dependent variables were analysed using paired t-tests and significance was accepted when P<.05. Data are presented as Mean± SD. VO2peak during the GXT was reduced post altitude training (Pre=3.67± 0.28, Post=3.55± 0.22 L.min-1, P<0.05), but neither threshold power (DMAX) nor any other peak GXT parameters (POpeak, HRpeak, HLApeak, pHmin) changed. In contrast, following altitude training, the following significant changes were observed in the RST: PO (Overall- 436± 32 to 478± 34 W, set2- 475± 37 to 495± 35 W), ¯ HLA (set2- 16.6± 2.5 to 13.9± 2.6 mM; set3- 18.3± 2.7 to 13.9 mM), pH (set1- 7.236± .056 to 7.276± .054), and ¯ %VO2peak (set1- 89.6± 3.2 to 85.6± 5.3%). The decrease in HR (» 3 bpm) during the RST was not significant. In this study, the adaptations to altitude training in female road cyclists were more apparent during RST than GXT. This observation supports the concept that altitude training can improve oxygen-independent (anaerobic) metabolic power systems.